Planning Strategies in Test Development: A Systematic Approach to Educational Evaluation - Arbeni, Wawan; Bilbina, Alzaiti; Karokaro, Yulia Intan Br; Wijaya, Dandi; Ginting, Ilham Ramadan; Harahap, Ade Irma Yunita (Holistic Science, 2025)
This study aims to analyze the systematic steps in test planning to enhance the quality of educational evaluation. The research method used is a literature review with a qualitative descriptive approach, integrating relevant theories and practices related to test planning. The findings indicate that effective test planning should involve determining the test's objectives, competency analysis, format selection, item writing, piloting, validation, and test analysis. The implementation of these steps ensures that the test meets the criteria of validity, reliability, objectivity, and practicality. This article provides significant contributions for educators in designing effective and efficient tests and offers new insights for further research in the field of educational evaluation.